Acetone sensor based on boron-doped cobaltosic oxide with amorphous / crystal heterostructure, preparation method and application thereof
By introducing amorphous/crystal heterostructure and boron doping into tricobalt oxide materials, acetone sensor with porous structures is solved, and the problem of insufficient gas sensitivity performance of tricobalt oxide materials when detecting acetone gas is achieved, high sensitivity and low detection limits are achieved. Acetone detection effect.
Patent Information
- Application Number
- CN202411277655.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The existing cobalt tetroxide materials have insufficient gas sensitivity when detecting acetone gas, and their microstructure needs to be improved to improve detection performance.
A boron-doped tricobalt tetraoxide material with amorphous/crystal heterostructure is used to react cobalt nitrate with sodium borohydride to form a material with a porous structure, and is prepared in combination with solution phase reaction and direct calcination method to form a resistance acetone sensor with ceramic tube structure .
It significantly improves the gas-sensitive performance of tricobalt oxide materials to acetone, achieves high sensitivity and low detection limits, and is suitable for portable detection instruments and on-site detection applications.
Smart Images

Figure CN119125244A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas sensors, and in particular relates to an acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure, a preparation method and application thereof in acetone detection. Background Art
[0002] Accurately detecting the concentration of acetone gas in the atmospheric environment has important research significance and practical value in the field of gas detection. On the one hand, acetone is a typical volatile organic compound that poses a serious threat to human health and has become a toxic and harmful gas that urgently needs to be detected. On the other hand, acetone can be used as a special exhaled marker and is expected to be used for the early diagnosis of diabetes. For example, the concentration of acetone in the exhaled breath of healthy people is 0.3-0.9ppm, while the concentration of acetone in the exhaled breath of diabetic patients is generally more than 1.8ppm. Therefore, accurate detection of acetone gas not only provides theoretical data for atmospheric environmental pollution monitoring and atmospheric environmental governance, but also provides a non-invasive detection technology for the diagnosis and monitoring of diabetes.
[0003] In the detection of gas-phase acetone, traditional analytical instruments represented by gas chromatography show the advantage of high precision. However, the large size and complex operation process make it difficult to use it to build portable detection instruments and on-site detection. On the contrary, resistive gas sensors with semiconductor oxides as the core provide a new method for detecting gas-phase acetone. In particular, this type of device has the advantages of low cost, simple structure, and easy device integration, and has become a rapidly developing gas detection technology. N-type semiconductor oxides represented by tin dioxide and zinc oxide show the advantages of high sensitivity and fast response speed in the detection of acetone, but the selectivity and stability of this type of device are poor. In recent years, p-type semiconductor materials represented by cobalt tetroxide have provided another idea for the detection of acetone. In particular, cobalt tetroxide materials show excellent catalytic activity in the reaction of catalytic oxidation of acetone, which provides a theoretical basis for the construction of high-performance acetone sensors. However, the gas sensitivity performance of cobalt tetroxide materials in the application of acetone detection needs to be further improved. Among them, regulating the microstructure of cobalt tetroxide materials is an effective way to improve their acetone sensing performance. Therefore, designing and preparing cobalt tetroxide materials with excellent gas-sensing properties is an important issue that needs to be solved urgently. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to integrate the unique structural advantages of an amorphous / crystalline heterostructure and the doping effect of boron atoms, improve the gas-sensitive performance of cobalt tetroxide materials to acetone, and provide an acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure, a preparation method, and an application in acetone detection, so as to solve the problems existing in the background technology.
[0005] The acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure described in the present invention is a ceramic tube structure, which is composed of an Al2O3 ceramic tube substrate, two parallel and mutually independent annular Au electrodes coated on the outer surface of the Al2O3 ceramic tube substrate, a gas sensitive film coated on the outer surface of the Al2O3 ceramic tube and the annular Au electrodes, and a nickel-chromium alloy heating coil passing through the inside of the Al2O3 ceramic tube; the material of the gas sensitive film is boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure, and the preparation steps are as follows:
[0006] (1) adding 1.0-3.0 g of cobalt nitrate powder to 200-300 mL of ethanol and stirring at room temperature for 2-3 h to obtain an aqueous solution of cobalt nitrate;
[0007] (2) adding 0.5-1.0 g of sodium borohydride to 30-50 mL of water and stirring at room temperature for 5-10 min to obtain an aqueous solution of sodium borohydride;
[0008] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 2 to 3 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate to obtain a dispersion of a solid mixture containing cobalt and boron;
[0009] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 50 to 60° C. for 30 to 50 minutes to obtain a solid mixture powder containing cobalt and boron;
[0010] (5) calcining the solid mixture powder containing cobalt and boron obtained in step (4) at 250-350° C. for 3-5 hours to obtain the boron-doped cobalt oxide material having an amorphous / crystalline heterostructure.
[0011] The Al2O3 ceramic tube used in the present invention has a length of 3-5 mm, an outer diameter of 1.1-1.3 mm, and an inner diameter of 0.7-0.9 mm; the nickel-chromium alloy heating coil provides the sensor with a working temperature, and the resistance of the heating coil is 30-40 Ω; the width of the annular Au electrode is 0.7-0.9 mm, the spacing between the two Au electrodes is 1.7-1.9 mm, the thickness of the Au electrode is 0.05-0.08 mm, and the thickness of the gas sensitive film is 180-220 μm; before and after the gas sensitive film contacts the gas to be measured, its resistance will change, and the sensitivity of the sensor can be obtained by measuring the change in resistance between the two annular Au electrodes. The sensitivity is calculated by dividing the resistance of the two annular Au electrodes in the air by their resistance in the target gas.
[0012] The method for preparing a resistive acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure according to the present invention comprises the following steps:
[0013] (1) mixing a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure with deionized water in a mass ratio of 3 to 5:1, and grinding the mixture into a paste slurry; coating the slurry on the surface of an Al2O3 ceramic tube having two parallel and separate annular Au electrodes on the outer surface;
[0014] (2) baking the device obtained in step (1) under an infrared lamp for 20 to 40 minutes, and after the sensitive material is dried, passing a nickel-chromium alloy heating coil with a resistance value of 30 to 40 Ω through the interior of the Al2O3 ceramic tube as a heating wire, and welding and packaging it according to the indirect heating gas sensor;
[0015] (3) The device obtained in step (2) is aged at 280-320° C. for 8-12 hours to obtain the boron-doped cobalt tetroxide resistive acetone sensor having an amorphous / crystalline heterostructure.
[0016] The advantages of the present invention are:
[0017] 1) The boron-doped cobalt tetroxide material with an amorphous / crystalline heterostructure in the present invention contains a unique amorphous / crystalline heterostructure, which not only maintains the stable structure of the crystalline material, but also can give play to the advantages of the amorphous structure such as a large degree of electron delocalization and a large number of reaction sites, thereby improving the acetone gas sensing performance of the cobalt tetroxide material;
[0018] 2) The boron-doped cobalt tetroxide material with an amorphous / crystalline heterostructure in the present invention contains boron atoms. Compared with traditional metal ion dopants, boron atoms, as non-metallic dopants, have large electronegativity and unique electronic structure, which endow cobalt tetroxide with unique structural characteristics;
[0019] 3) The present invention utilizes the gas generated by the reaction of cobalt nitrate and sodium borohydride as a template to hinder the agglomeration of cobalt oxide nanostructures, and the obtained material has a rich porous structure;
[0020] 4) The present invention adopts a method combining solution phase reaction and direct calcination to prepare a boron-doped cobalt oxide material with an amorphous / crystalline heterostructure. The preparation method is simple, efficient, high in yield, and suitable for mass production;
[0021] 5) The boron-doped cobalt tetroxide sensor with an amorphous / crystalline heterostructure prepared by the present invention has high sensitivity and low detection limit to acetone and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is an X-ray diffraction pattern of boron-doped cobalt oxide having an amorphous / crystalline heterostructure prepared in Example 1;
[0023] Figure 2 are transmission electron microscope photographs of boron-doped cobalt oxide with an amorphous / crystalline heterostructure prepared in Example 1 at different magnification ratios; Figure 2 The scale bar in (a) is 100 nm. Figure 2 The scale bar in (b) is 5 nm;
[0024] Figure 3 The amorphous / crystalline heterojunction boron-doped cobalt tetraoxide O1s prepared in Example 1 ( Figure 3 (a)) and B1s peak ( Figure 3 (b));
[0025] Figure 4 is a temperature-programmed desorption curve of oxygen for the amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1;
[0026] Figure 5 is a temperature-programmed reduction curve of the amorphous / crystalline heterojunction boron-doped cobalt tetroxide to hydrogen prepared in Example 1;
[0027] Figure 6 is the response recovery curve of the acetone sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 to 100 ppm acetone at 190° C.;
[0028] Figure 7 is the response recovery curve of the acetone sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 to 20-140 ppb acetone at 190° C.;
[0029] Figure 8 are eight consecutive response recovery curves of the acetone sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 to 100 ppm acetone at 190° C.;
[0030] Fig. 9 is the response recovery curve of the acetone sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 2 to 100 ppm acetone at 190° C.;
[0031] Fig.10 is the response recovery curve of the acetone sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 3 to 100 ppm acetone at 190° C.;
[0032] Fig.11is the response recovery curve of the acetone sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 4 to 100 ppm acetone at 190° C.;
[0033] The X-ray diffraction pattern of boron-doped cobalt oxide with amorphous / crystalline heterostructure prepared in Example 1 is as follows: Figure 1 As shown. Different from the standard crystal diffraction peaks of perfect cobalt oxide, boron-doped cobalt oxide with an amorphous / crystalline heterostructure gives two weaker diffraction peaks at 36.6° and 66.2°, and the diffraction intensity of the diffraction peaks is low and the spectrum peaks are broad, indicating that the prepared material has poor crystallinity. The reason for this result is that an amorphous / crystalline heterostructure is formed inside the material.
[0034] The transmission electron microscope photo of the boron-doped cobalt oxide with amorphous / crystalline heterostructure prepared in Example 1 is as follows: Figure 2 As shown. From the low-power electron microscope photo ( Figure 2 (a)) shows that the boron-doped cobalt oxide with amorphous / crystalline heterostructure is a typical lamellar structure. From the high-magnification transmission electron microscopy photo ( Figure 2 (b)) It can be seen that the material is composed of crystalline structure and amorphous structure, indicating the formation of an amorphous / crystalline heterostructure;
[0035] The O1s and B1s spectra of boron-doped cobalt tetroxide with amorphous / crystalline heterostructure prepared in Example 1 are as follows: Figure 3 As shown, from Figure 3 (a) It can be seen that the oxygen element in the material is composed of lattice oxygen, oxygen vacancies and surface adsorbed oxygen. Due to the existence of amorphous and crystalline heterogeneous structures in the material, the content of oxygen vacancies in the material is relatively high. B 1s peak ( Figure 3 (b)) indicates that the B element is indeed doped into the structure of cobalt tetroxide, and the boron element exists in the form of BO bond;
[0036] The temperature-programmed desorption curve of oxygen for the amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 is as follows: Figure 4 As shown, it can be seen that the material contains oxygen species with three structures: adsorbed oxygen, surface vacancy oxygen and lattice oxygen;
[0037] The temperature-programmed reduction curve of the amorphous / crystalline heterojunction boron-doped cobalt tetroxide to hydrogen prepared in Example 1 is as follows: Figure 5 As shown. It can be seen that with the increase of temperature, three reduction peaks can be observed, corresponding to the reduction of Co 3+ To Co 2+ , reduction of Co 2+ to Co and reduce B2O3 to B;
[0038] The response recovery transient curve of the acetone gas sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 to 100 ppm acetone at 190°C is as follows: Figure 6 As shown. It can be seen that the sensor has obvious response characteristics to acetone. By analyzing the ratio of the device's resistance value in acetone to the resistance value in air, it is calculated that the device's response value reaches 106;
[0039] The response recovery transient curve of the acetone gas sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 to 20-140 ppb acetone at 190°C is as follows: Figure 7 As shown. It can be seen that with the increase of acetone concentration, the response value of the sensor gradually increases. The sensor also shows fast response recovery characteristics to low concentration acetone. The lowest detection concentration of the device is 20ppb.
[0040] The response repeatability curve of the acetone gas sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 1 to 100 ppm acetone at 190°C is shown in FIG. Figure 8 It can be seen that the amorphous / crystalline heterojunction boron-doped cobalt tetroxide sensor shows a stable and repeated response when repeatedly exposed to 100 ppm acetone, indicating that the sensor has excellent repeatability;
[0041] The response recovery transient curve of the acetone gas sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 2 to 100 ppm acetone at 190°C is as follows: Fig. 9 As shown. It can be seen that the sensor has good response and recovery characteristics to acetone;
[0042] The response recovery transient curve of the acetone gas sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 3 to 100 ppm acetone at 190°C is as follows: Fig.10 As shown. It can be seen that the sensor has good response and recovery characteristics to 100ppm acetone;
[0043] The response recovery transient curve of the acetone gas sensor based on amorphous / crystalline heterojunction boron-doped cobalt tetroxide prepared in Example 4 to 100 ppm acetone at 190°C is as follows: Fig.11 It can be seen that the sensor has good response and recovery characteristics to 100ppm acetone. DETAILED DESCRIPTION
[0044] The present invention is further described below with reference to the accompanying drawings and embodiments.
[0045] Example 1
[0046] (1) Add 1.0 g of cobalt nitrate powder to 200 mL of ethanol and stir at room temperature for 3 h to obtain an aqueous solution of cobalt nitrate;
[0047] (2) adding 0.5 g of sodium borohydride to 50 mL of water and stirring at room temperature for 5 min to obtain an aqueous solution of sodium borohydride;
[0048] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 3 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate, and obtaining a dispersion of a solid mixture containing cobalt and boron;
[0049] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 50° C. for 50 minutes to obtain a solid mixture powder containing cobalt and boron;
[0050] (5) The solid mixture powder containing cobalt and boron obtained in step (4) was calcined at 350° C. for 5 h to obtain a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure, with a product mass of 0.27 g; (6) The cobalt ion-doped cerium dioxide aerogel material prepared in step (5) was mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which was coated on the surface of an Al2O3 ceramic tube having two parallel, annular and separate gold electrodes on the outer surface. After baking for 20 minutes under an infrared lamp, a sensitive film based on cobalt ion-doped cerium dioxide aerogel was obtained on the surface of the ceramic tube, and the thickness of the sensitive film was 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω was passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube was 3mm, the outer diameter was 1.1mm, and the inner diameter was 0.7mm; the width of the annular Au electrode was 0.7mm, and the distance between the two electrodes was 1.7mm;
[0051] (7) The acetone gas sensor based on the cobalt ion-doped cerium dioxide aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the cobalt ion-doped cerium dioxide aerogel material.
[0052] Example 2
[0053] (1) Add 1.0 g of cobalt nitrate powder to 200 mL of ethanol and stir at room temperature for 3 h to obtain an aqueous solution of cobalt nitrate;
[0054] (2) Add 1.0 g of sodium borohydride to 40 mL of water and stir at room temperature for 5 min to obtain an aqueous solution of sodium borohydride;
[0055] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 3 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate, and obtaining a dispersion of a solid mixture containing cobalt and boron;
[0056] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 50° C. for 50 minutes to obtain a solid mixture powder containing cobalt and boron;
[0057] (5) The solid mixture powder containing cobalt and boron obtained in step (4) was calcined at 350° C. for 3 h to obtain a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure, with a product mass of 0.26 g; (6) The cobalt ion-doped cerium dioxide aerogel material prepared in step (5) was mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which was then coated on the surface of an Al2O3 ceramic tube having two parallel, annular and separate gold electrodes on the outer surface. After baking for 20 minutes under an infrared lamp, a sensitive film based on cobalt ion-doped cerium dioxide aerogel was obtained on the surface of the ceramic tube, and the thickness of the sensitive film was 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω was passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube was 3mm, the outer diameter was 1.1mm, and the inner diameter was 0.7mm; the width of the annular Au electrode was 0.7mm, and the distance between the two electrodes was 1.7mm;
[0058] (7) The acetone gas sensor based on the cobalt ion-doped cerium dioxide aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the cobalt ion-doped cerium dioxide aerogel material.
[0059] Example 3
[0060] (1) Add 2.0 g of cobalt nitrate powder to 200 mL of ethanol and stir at room temperature for 3 h to obtain an aqueous solution of cobalt nitrate;
[0061] (2) adding 0.5 g of sodium borohydride to 30 mL of water and stirring at room temperature for 5 min to obtain an aqueous solution of sodium borohydride;
[0062] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 3 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate, and obtaining a dispersion of a solid mixture containing cobalt and boron;
[0063] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 60° C. for 30 minutes to obtain a solid mixture powder containing cobalt and boron;
[0064] (5) calcining the solid mixture powder containing cobalt and boron obtained in step (4) at 300° C. for 5 h to obtain a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure, with a product mass of 0.50 g; (6) mixing the copper ion-doped cerium dioxide aerogel material prepared in step (5) with deionized water in a mass ratio of 3:1, and grinding them into a paste slurry, which is then coated on the surface of an Al2O3 ceramic tube having two parallel, annular and separate gold electrodes on the outer surface. After baking for 20 minutes under an infrared lamp, a sensitive film based on copper ion-doped cerium dioxide aerogel was obtained on the surface of the ceramic tube, and the thickness of the sensitive film was 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω was passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube was 3mm, the outer diameter was 1.1mm, and the inner diameter was 0.7mm; the width of the annular Au electrode was 0.7mm, and the distance between the two electrodes was 1.7mm;
[0065] (7) The acetone gas sensor made of the copper metal ion-doped ceria aerogel material obtained in step (6) is subjected to an aging treatment at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the copper ion-doped ceria aerogel material.
[0066] Example 4
[0067] (1) Add 2.0 g of cobalt nitrate powder to 300 mL of ethanol and stir at room temperature for 2 h to obtain an aqueous solution of cobalt nitrate;
[0068] (2) Add 1.0 g of sodium borohydride to 50 mL of water and stir at room temperature for 10 min to obtain an aqueous solution of sodium borohydride;
[0069] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 2 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate, and obtaining a dispersion of a solid mixture containing cobalt and boron;
[0070] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 60° C. for 30 minutes to obtain a solid mixture powder containing cobalt and boron;
[0071] (5) The solid mixture powder containing cobalt and boron obtained in step (4) was calcined at 300° C. for 3 h to obtain a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure, with a product mass of 0.54 g; (6) The copper ion-doped cerium dioxide aerogel material prepared in step (5) was mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which was coated on the surface of an Al2O3 ceramic tube having two parallel, annular and separate gold electrodes on the outer surface. After baking for 20 minutes under an infrared lamp, a sensitive film based on copper ion-doped cerium dioxide aerogel was obtained on the surface of the ceramic tube, and the thickness of the sensitive film was 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω was passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube was 3mm, the outer diameter was 1.1mm, and the inner diameter was 0.7mm; the width of the annular Au electrode was 0.7mm, and the distance between the two electrodes was 1.7mm;
[0072] (7) The acetone gas sensor made of the copper metal ion-doped ceria aerogel material obtained in step (6) is subjected to an aging treatment at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on the copper ion-doped ceria aerogel material.
[0073] Example 5
[0074] (1) Add 3.0 g of cobalt nitrate powder to 300 mL of ethanol and stir at room temperature for 2 h to obtain an aqueous solution of cobalt nitrate;
[0075] (2) adding 0.5 g of sodium borohydride to 40 mL of water and stirring at room temperature for 10 min to obtain an aqueous solution of sodium borohydride;
[0076] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 2 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate, and obtaining a dispersion of a solid mixture containing cobalt and boron;
[0077] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 50° C. for 40 minutes to obtain a solid mixture powder containing cobalt and boron;
[0078] (5) The solid mixture powder containing cobalt and boron obtained in step (4) was calcined at 250° C. for 5 h to obtain a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure, with a product mass of 0.79 g; (6) The manganese ion-doped cerium dioxide aerogel material prepared in step (5) was mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which was then coated on the surface of an Al2O3 ceramic tube having two parallel, annular and separate gold electrodes on the outer surface. After baking for 20 minutes under an infrared lamp, a sensitive film based on manganese ion-doped cerium dioxide aerogel was obtained on the surface of the ceramic tube, and the thickness of the sensitive film was 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω was passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube was 3mm, the outer diameter was 1.1mm, and the inner diameter was 0.7mm; the width of the annular Au electrode was 0.7mm, and the distance between the two electrodes was 1.7mm;
[0079] (7) The acetone gas sensor based on manganese ion-doped ceria aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on manganese ion-doped ceria aerogel material.
[0080] Example 6
[0081] (1) Add 3.0 g of cobalt nitrate powder to 300 mL of ethanol and stir at room temperature for 2 h to obtain an aqueous solution of cobalt nitrate;
[0082] (2) Add 1.0 g of sodium borohydride to 30 mL of water and stir at room temperature for 10 min to obtain an aqueous solution of sodium borohydride;
[0083] (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 2 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate, and obtaining a dispersion of a solid mixture containing cobalt and boron;
[0084] (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 60° C. for 40 minutes to obtain a solid mixture powder containing cobalt and boron;
[0085] (5) The solid mixture powder containing cobalt and boron obtained in step (4) is calcined at 250° C. for 3 h to obtain a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure, with a product mass of 0.80 g; (6) The manganese ion-doped cerium dioxide aerogel material prepared in step (5) is mixed with deionized water in a mass ratio of 3:1, and ground into a paste slurry, which is then coated on the surface of an Al2O3 ceramic tube having two parallel, annular and separate gold electrodes on the outer surface. After baking for 20 minutes under an infrared lamp, a sensitive film based on manganese ion-doped cerium dioxide aerogel was obtained on the surface of the ceramic tube, and the thickness of the sensitive film was 180μm; then a nickel-chromium alloy heating coil with a resistance value of 30Ω was passed through the Al2O3 ceramic tube as a heating wire, and finally welded and packaged according to the indirect heating gas sensor; the length of the Al2O3 ceramic tube was 3mm, the outer diameter was 1.1mm, and the inner diameter was 0.7mm; the width of the annular Au electrode was 0.7mm, and the distance between the two electrodes was 1.7mm;
[0086] (7) The acetone gas sensor based on manganese ion-doped ceria aerogel material obtained in step (6) is aged at 280° C. for 12 hours to complete the aging treatment of the gas sensor, thereby obtaining a resistive acetone sensor based on manganese ion-doped ceria aerogel material.
Claims
1. A boron-doped cobalt tetroxide acetone sensor with an amorphous / crystalline heterostructure, composed of Al 2 O 3 Ceramic tube substrate, coated on Al 2 O 3 Two parallel and separate annular Au electrodes on the outer surface of the ceramic tube substrate, coated on Al 2 O 3 The gas sensitive film on the outer surface of the ceramic tube and the annular Au electrode passes through the Al 2 O 3 It consists of a nickel-chromium alloy heating coil inside the ceramic tube; Features: The material of the gas sensitive film is boron-doped cobalt oxide with an amorphous / crystalline heterostructure, and the preparation steps are as follows: (1) adding 1.0-3.0 g of cobalt nitrate powder to 200-300 mL of ethanol and stirring at room temperature for 2-3 h to obtain an aqueous solution of cobalt nitrate; (2) adding 0.5-1.0 g of sodium borohydride to 30-50 mL of water and stirring at room temperature for 5-10 min to obtain an aqueous solution of sodium borohydride; (3) adding the aqueous solution of sodium borohydride obtained in step (2) to the aqueous solution of cobalt nitrate obtained in step (1), stirring at room temperature for 2 to 3 hours, so that a redox reaction occurs between the sodium borohydride and the cobalt nitrate to obtain a dispersion of a solid mixture containing cobalt and boron; (4) centrifugally collecting the dispersion of the solid mixture containing cobalt and boron obtained in step (3) to obtain a solid product, and then washing the solid product with water and ethanol for multiple times, placing it in a constant temperature drying oven, and drying it at 50 to 60° C. for 30 to 50 minutes to obtain a solid mixture powder containing cobalt and boron; (5) calcining the solid mixture powder containing cobalt and boron obtained in step (4) at 250-350° C. for 3-5 hours to obtain the boron-doped cobalt oxide material having an amorphous / crystalline heterostructure.
2. An acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure as claimed in claim 1, Features: Al 2 O 3 The length of the ceramic tube is 3 to 5 mm, the outer diameter is 1.1 to 1.3 mm, and the inner diameter is 0.7 to 0.9 mm; the nickel-chromium alloy heating coil provides the working temperature for the sensor, and the resistance of the heating coil is 30 to 40 Ω; the width of the annular Au electrode is 0.7 to 0.9 mm, the distance between the two Au electrodes is 1.7 to 1.9 mm, and the thickness of the Au electrode is 0.05 to 0.08 mm.
3. An acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure as claimed in claim 1, Features: The thickness of the gas sensitive film is 180-220 μm.
4. A method for preparing an acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure according to any one of claims 1 to 3, the steps of which are as follows: (1) mixing a boron-doped cobalt oxide material having an amorphous / crystalline heterostructure with deionized water in a mass ratio of 3 to 5:1 and grinding the mixture into a paste slurry; coating the paste on an Al substrate having two parallel and separate annular Au electrodes on its outer surface; 2 O 3 Ceramic tube surface; (2) The device obtained in step (1) is baked under an infrared lamp for 20 to 40 minutes. After the sensitive material is dried, a nickel-chromium alloy heating coil with a resistance value of 30 to 40 Ω is passed through the Al 2 O 3 The interior of the ceramic tube is used as a heating wire and is welded and packaged as a side-heated gas sensor. (3) The device obtained in step (2) is aged at 280-320° C. for 8-12 hours to obtain the boron-doped cobalt tetroxide resistive acetone sensor having an amorphous / crystalline heterostructure.
5. Use of an acetone sensor based on boron-doped cobalt tetroxide with an amorphous / crystalline heterostructure as claimed in any one of claims 1 to 3 in acetone detection.
Citation Information
Patent Citations
Palladium / cobaltosic oxide-graphene thin film for detecting very-low-concentration acetone at low temperature
CN109459470A
Self-supporting boron-doped diamond electrochemical sensor and preparation method and application thereof
CN111948266A
Fluoro borate modified metal oxide gas-sensitive material as well as preparation method and application thereof
CN115078475A
Gas Sensor Element
US20150346190A1
Gas Sensor Element
US20170146504A1
